DEVELOPMENT AND ASSIGNMENT TO THE POSITION BASED ON THE RESULTS OF ASSESSING THE COMPETENCIES OF LEADERSHIP PERSONNEL - Rafikova , Ziyodakhon (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
In any state body and institution, the appointment of employees to worthy positions based on the assessment of their management potential ensures the sustainable development of the organization. The administrative reforms being implemented in Uzbekistan are setting new tasks for state bodies and civil servants. To increase the effectiveness of the reforms being implemented, one of the urgent tasks today is to create a reserve of highly potential managerial personnel, to form in them competencies that will allow them to adapt to changes in the life of the state and society.